Population of the World - Arsenović, Daniela (Demographic Challenges in Central Europe: Legal and Family Policy Response, 2024)
The world population passed 1 billion for the first time in history in the first half of the 19th century. Since then, the global population has continued to grow, and most regions and countries are experiencing rapid and broad demographic change. In 2022, the world population reached about 7.9 billion people, and according to the current projections developed by the United Nations, it could grow to approximately 9.7 billion in 2050. Until the middle of the 21st century, population growth rates will differ by region, and Central and Southeast Asia will be the most populated areas. A high increase in population is also expected to occur in sub-Saharan Africa, whereas Europe will reach a population peak during the 2030s, with the European population declining until 2050 owing to a low fertility level. With declines in fertility, the world’s population is ageing. In 2018, the number of persons in the world aged 65 and over was higher than the number of children under five for the first time. All regions will experience ageing, with faster progress in developing countries than has historically been observed in developed regions. The projected trends in the world population are a common result of population momentum, future levels of fertility and mortality, and regional migration flows. The contribution of these components to future population trends will vary by region and country.Keywords: demographic change, population growth, fertility, mortality, international migration